SENI MURAL SEBAGAI MEDIA PENDIDIKAN GUNA MENCEGAHVANDALISME DI SMA NEGERI 5 YOGYAKARTA - dan Diyan Fatimatuz Zahra, Ida Yeni R., Safrina Arifiani F., (Pelita - Jurnal Penelitian Mahasiswa UNY, 2009)
This research is intended to reduce the acts of vandalism by covering the wall withan inspirational mural as educational media in SMA N 5 Yogyakarta. The reason ofchoosing this school is because there are some vandalism actions there. This action isthe effect of the students’ hobbies in drawing on the everywhere wall or facilities of thisschool.This research focused on the reducing vandalism action through mural arts. It iseffective because the student can draw in the wall or any other places in that school.Through this activity, the creativity and the talent of the students will increase. Thetechniques of collecting the data were done by having observation, field note, anddocumentation. This research employed qualitative method.The result of the research shows that this program has been successful in reducingvandalism in this school. The students are accustomed to doing the productive activities.In addition, mural arts offer many other advantages like entertainment, creativity, goodworks, and the accessories of Yogyakarta Municipality. This art has been a uniquesymbol of Yogyakarta. At last, this action is not only as a hobby but also as a businessmotivator.Key Words : Mural arts, Educational media, Vandalism